2017
DOI: 10.1371/journal.pone.0185466
|View full text |Cite
|
Sign up to set email alerts
|

Status and determinants of small farming households' food security and role of market access in enhancing food security in rural Pakistan

Abstract: In most of the developing countries, lack of resources and little market accessibility are among the major factors that affect small farming household food security. This study aims to investigate the status of small farming households’ food security, and its determinants including the role of market accessibility factors in enhancing food security at household level. In addition, this study also determines the households’ perception about different kinds of livelihoods risks. This study is based on a househol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
75
1
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(106 citation statements)
references
References 20 publications
10
75
1
9
Order By: Relevance
“…Quality and access to infrastructure and communication facilities in rural areas are modified by distance to cities in India and Ethiopia [129,137]. Moreover, distance to urban markets and metaled roads influence the livelihood security of rural households [139]. Studies on the vulnerability of city sizes suggested that larger cities are less vulnerable to hazards compared to small cities as they have more social, economic, physical, and institutional resources to deal with hazards [15,[140][141][142].…”
Section: Spatial Patternmentioning
confidence: 99%
“…Quality and access to infrastructure and communication facilities in rural areas are modified by distance to cities in India and Ethiopia [129,137]. Moreover, distance to urban markets and metaled roads influence the livelihood security of rural households [139]. Studies on the vulnerability of city sizes suggested that larger cities are less vulnerable to hazards compared to small cities as they have more social, economic, physical, and institutional resources to deal with hazards [15,[140][141][142].…”
Section: Spatial Patternmentioning
confidence: 99%
“…More so, growing population coupled with increased intensity of environmental extreme events like floods, droughts, extreme variability in temperature and rainfall has increased the pressure on the current food production systems which in turn, has threatened the current food security crisis in most of the developing countries [13]. Due to higher food demands and reduced crop productivity, the higher food prices may further negatively affect the food access and availability for low income and already poor households [14].…”
Section: Introductionmentioning
confidence: 99%
“…Determinats of food security and role of various socio-economic factors in ensuring food security were estimated taking insights from various studies on the subject for other locations of the world [17,40,42,47,[50][51][52][53][54][55]].…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…This study used two levels of protein intake, i.e. 50 grams and 70 grams for ensuring protein security [3,17,42,50,57,58]. According to household's information, value 1 was used for protein secure households while otherwise 0 for rest.…”
Section: Mathematical Computationsmentioning
confidence: 99%
See 1 more Smart Citation